2017
DOI: 10.1186/s12877-017-0508-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of frailty among community dwelling older adults in receipt of low level home support: a cross-sectional analysis of the North Dublin Cohort

Abstract: BackgroundThere is increasing demand for formal government funded home help services to support community-dwelling older people in Ireland, yet limited information exists on the health profiles of this group, especially regarding frailty. Our aim was to profile a large cohort of adults in receipt of low level home help and to determine the prevalence of frailty.MethodsA total 1312 older adults, (≥ 65 years) in receipt of low level home help (< 5 h per week) were reviewed by community nurses and frailty was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
(58 reference statements)
3
26
0
Order By: Relevance
“…In our study, we found that both sarcopenia and frailty were significantly more common in PD patients compared with the general elderly population. The prevalence rates of sarcopenia and frailty in our general population-based sample were within previously reported ranges, contributing to the validity of the screening tools used [4,[6][7][8][9][10][11][12]. The prevalence rates of sarcopenia and frailty were slightly lower in the community-based PD cohort compared to the PD cohort recruited in the tertiary center.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, we found that both sarcopenia and frailty were significantly more common in PD patients compared with the general elderly population. The prevalence rates of sarcopenia and frailty in our general population-based sample were within previously reported ranges, contributing to the validity of the screening tools used [4,[6][7][8][9][10][11][12]. The prevalence rates of sarcopenia and frailty were slightly lower in the community-based PD cohort compared to the PD cohort recruited in the tertiary center.…”
Section: Discussionsupporting
confidence: 76%
“…There is evidence that reduced activities of daily living (ADL) activity is associated with functional deterioration, LTC, and mortality among older people. 23,24 There have been no studies done on the identification of factors that influence admission to long-stay care in Ireland, or on predictors of mortality among community-dwelling older dependent adults. 20 In a systematic review and meta-analysis, Cepoiu-Martin et al found that increased age, functional impairment, behavioural, and psychological problems and being in the severe stages of dementia were significant predictors of LTC placement for people with dementia.…”
Section: Key Pointsmentioning
confidence: 99%
“…Scores range from 0 to 20, with a lower score indicating a higher level of dependency. For the purposes of analysis in this study and as used in our previous study, 23 these five categories were collapsed into two: no communication difficulties, which included those recorded as having "no problems" and communication difficulties, which included all others. From the overall score, an individual is categorised as maximum dependency (0-5), high dependency (6-10), medium dependency (11)(12)(13)(14)(15), low dependency (16)(17)(18)(19), and independent (20).…”
Section: Study Variablesmentioning
confidence: 99%
See 2 more Smart Citations